2010
DOI: 10.5272/jimab.1522009_119
|View full text |Cite
|
Sign up to set email alerts
|

ENDODONTIC TREATMENT OF A SECOND MAXILLARY MOLAR WITH FIVE ROOT CANALS – A Case Report

Abstract: ITRODUCTION: Knowledge of the internal dental morphology is a complex and extremely important point for planning and performing of endodontic treatment.CASE REPORT: The subject of this study was a clinical case of a second maxillary molar with five root canals -one canal in the palatal root, one canal in the distobuccal root and three canals in mesiobuccal root.DISCUSSION: Successful root canal treatment depends on proper cleaning, shaping and compact filling of the root canal under aseptic conditions. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…Therefore, it is prudent to better understand the tooth root morphology by means of 3D imaging technology to anticipate the challenge of root canal treatment. It has been reported that when extracanals in the mesiobuccal root are suspected, the access cavity should be modified to locate their potential canal orifices [ 32 , 33 ]. Based on the present results, the cavity modification should be limited not only to horizontal extension of the cavity but also to apical extension which is represented as floor troughing, to expose the buried canal orifices in the mesiobuccal root area, if present [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is prudent to better understand the tooth root morphology by means of 3D imaging technology to anticipate the challenge of root canal treatment. It has been reported that when extracanals in the mesiobuccal root are suspected, the access cavity should be modified to locate their potential canal orifices [ 32 , 33 ]. Based on the present results, the cavity modification should be limited not only to horizontal extension of the cavity but also to apical extension which is represented as floor troughing, to expose the buried canal orifices in the mesiobuccal root area, if present [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that when extracanals in the mesiobuccal root are suspected, the access cavity should be modified to locate their potential canal orifices [ 32 , 33 ]. Based on the present results, the cavity modification should be limited not only to horizontal extension of the cavity but also to apical extension which is represented as floor troughing, to expose the buried canal orifices in the mesiobuccal root area, if present [ 32 , 33 ]. However, the chamber floor should not be troughed more than 2 mm to avoid jeopardizing the tooth integrity and possible tooth perforation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…When extra canals in the MBR are suspected, the access opening is extended on the mesial side to have a trapezoidal rather than a triangular shape (36,40,41,48,51,56). Next, the clinician should read the "road map" of the pulpal floor to locate potential canal orifices.…”
Section: Careful Examination Of Preoperative and Working Radiographs mentioning
confidence: 99%
“…Next, the clinician should read the "road map" of the pulpal floor to locate potential canal orifices. This may include exploring the floor with an endodontic explorer (29,31,36,37,39,42,55,58), troughing the floor with round burs (31,36) or ultrasonic tips (41,49,56). In addition, staining the pulpal floor with a dye, performing the champagne test with sodium hypochlorite, visualizing canal bleeding points are important aids in locating canal orifices (2).…”
Section: Careful Examination Of Preoperative and Working Radiographs mentioning
confidence: 99%
“…The occurrence of 0.9 percent with a single root in the maxillary second molar was reported in an Indian population survey, but none with a single root canal was reported. (Gusiyska, 2010;Di Ventura et al, 2019)). Searching for a missing canal can result in iatrogenic mishaps, such as perforation or premature removal of the tooth(Table 2).…”
Section: Variation S In Number Of Canalsmentioning
confidence: 99%